The optimal ratio of apparent digestible valine to lysine to maximize growth performance of the nursery pig - B W James; J C Woodworth; Robert D Goodband; Michael D Tokach; Jim L Nelssen; Joel M DeRouchey; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2001)
A total of 210 nursery pigs (initially 19.6 lb and approximately 28 d of age) were used in a 21-d growth assay to determine the optimal ratio of valine to lysine to maximize growth performance. The seven treatments consisted of a basal diet (14.2% CP; 1.07% apparent digestible lysine) with increasing ratios of valine:lysine (48, 53, 58, 63, 69, and 74%) and a negative control containing 0.97% lysine and 0.79% apparent digestible valine. Results indicate that the optimal apparent digestible valine:lysine ratio for the nursery pig is 58 and 64% for ADG and F/G, respectively. Therefore, most typical nursery diets will contain adequate amounts of valine to maximize growth performance of nursery pigs.; Swine Day, Manhattan, KS, November 15, 2001
Keywords: Swine day; 2001; Kansas Agricultural Experiment Station contribution; no. 02-132-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 880; Swine; Valine; Lysine; Nursery Pig